Tip 2 diabetes mellitus' lu olgularda vücut ağırlığının fiziksel aktivite düzeyi, fonksiyonel kapasite, denge ve yaşam kalitesine etkisi / The effect of body weight on physical activity level, functional capacity, balance and quality of life in cases with type 2 diabetes mellitus - Topçu, Şule (Bezmialem Vakıf University, 2019)
Our study was carried out to investigate the effect of body weight on physical activity level, functional capacity, balance and quality of life in patients with type 2 diabetes. In the study, 50 volunteer patients (52,90 ± 9,27 years) who were admitted to the internal medicine and dietary outpatient clinic of Eyüp Sultan Supplement Service Building of Bezmialem Vakif University Hospital, took place. Individuals were evaluated by prospective and face to face interview method. Body composition analysis (Omron Body Composition Monitor), waist-hip circumference, lower limb muscle strengths (Muscle Hand Held dynamometer), gripping strengths (Hand Grip), physical activity levels (International Physical Activity Questionnaire-Short Form), functional capacities (6 Minutes Walk Test), balance (Biodex Balance System), clinical balance (Berg Balance Scale), quality of life (Nottingham Health Profile) and disease-specific quality of life (Diabetes Quality of Life Scale) were evaluated. IBM SPSS Statistic 20 was used for statistical analysis. A statistically significant relationship was found between BMI and body fat ratio (p 0,000), skeletal muscle mass (p 0,000), visceral fat ratio (p 0,000), waist circumference (p 0,000), hip circumference (p 0,000), waist / hip ratio (p 0,035), grip strength (p 0,045), 6 min walking distance (p 0,000), Berg balance score (p 0,012), total score of Nottingham Health Profile (p 0,006) furthermore pain (p 0,000), sleep (p 0,041), physical activity (p 0,000), which are sub-parameter of Nottingham Health Profile. A statistically significant relationship was not found between BMI and lower extremity muscle strength, International Physical Activity Scale, Biodex balance scores and Diabetes Quality of Life Scale. When the patients were grouped according to their BMI, the pain perception of the obese group was higher than the normal weight (p 0,037). In conclusion, this study showed that high body weight in patients with type 2 diabetes negatively affected functional capacity, clinical balance and quality of life. Keywords: type 2 diabetes mellitus, body mass index, physical activity level, functional capacity, balance, quality of life.
Çalışmamız tip 2 diyabetli hastalarda vücut ağırlığının fiziksel aktivite düzeyi, fonksiyonel kapasite, denge ve yaşam kalitesine etkisini incelemek amacıyla yapıldı. Çalışmada Bezmialem Vakıf Üniversitesi Hastanesi Eyüp Sultan Ek Hizmet Binası iç hastalıkları ve diyet polikliniğine başvuran ve dahil edilme kriterlerimize uyan 50 gönüllü hasta (52,90±9,27 yıl) yer aldı. Bireyler prospektif ve yüzyüze görüşme yöntemi ile değerlendirildi. Hastaların vücut kompozisyonu analizi (Omron Body Composition Monitör), bel-kalça çevresi, alt ekstremite kas kuvvetleri (Muscle Hand Held dinamometre), kavrama kuvvetleri (Hand Grip), fiziksel aktivite düzeyleri (Uluslararası Fiziksel Aktivite Anketi-Kısa Form), fonksiyonel kapasiteleri (6 Dakika Yürüme Testi), dengeleri (Biodex Balance System), klinik dengeleri (Berg Denge Ölçeği), yaşam kaliteleri (Nottingham Sağlık Profili) ve hastalığa özgü yaşam kaliteleri (Diyabet Yaşam Kalitesi Ölçeği) değerlendirildi. İstatistiksel analizler için IBM SPSS Statistic 20 kullanıldı. Hastaların VKİ ile vücut yağ oranı (p 0,000), iskelet kas kitlesi oranı (p 0,000), viseral yağ oranı (p 0,000), bel çevresi (p 0,000), kalça çevresi (p 0,000), bel/kalça oranı (p 0,035), kavrama kuvveti (p 0,045), 6 dakika yürüme mesafesi (p 0,000), Berg denge skoru (p 0,012) ve Nottingham Sağlık profili genel skorunda (p 0,006), ağrı (p 0,000), uyku (p 0,041), fiziksel aktivite (p 0,000) alt grupları arasında anlamlı ilişki bulundu. Hastaların VKİ ile alt ekstremite kas kuvveti, Uluslararası Fiziksel Aktivite Ölçeği, Biodex denge skorları ve Diyabet Yaşam Kalitesi Ölçeği arasında istatistiksel olarak anlamlı ilişki saptanmadı. Hastalar VKİ'lerine göre gruplandırıldığında obez grubun ağrı algısının normal kilolulardan fazla olduğu belirlendi (p 0,037). Sonuç olarak bu çalışma tip 2 diyabetli hastalarda vücut ağırlığının fazla olmasının fonksiyonel kapasite, klinik denge ve yaşam kalitesini olumsuz etkilediğini gösterdi.
Keywords: Fizyoterapi ve Rehabilitasyon = Physiotherapy and Rehabilitation; Denge = Equilibrium; Diabetes mellitus = Diabetes mellitus; Diabetes mellitus-tip 2 = Diabetes mellitus-type 2; Fiziksel aktivite = Physical activity; Fizyolojik kapasite = Physiological capacity; Postural denge = Postural balance; Vücut ağırlığı = Body weight; Vücut kitle indeksi = Body mass index; Yaşam kalitesi = Quality of life